Controlled Distribution or Unlimited Overexertion? The Interdisciplinary Striving for Excess and Transgression (KULT_online, 2012)
From an interdisciplinary point of view, comprehensive volume on the cultural practice of overexertion aims at opening up the vast territory of the concept of overexertion. The authors meet their stated goal of enhancing complexity. Thereby, overexertion is defined as something which exceeds limits on the threshold of containment. The authors' emphasis on liminal aspects of overexertion elucidates how difficult it is to think about excess at all. Due to the large quantity of articles concerning philology, media studies, the arts, and sociology, the perspective on one-dimensional overexertion as part of the gift, as analysed elsewhere by Marcel Mauss and enforced especially by philosophy, is hardly taken into account.